Bird-Repellent Machine: Reducing Birds’ Feces - Mohd Ruzaimi, Daniel Aiman; Rafiq Iqbal, Ahmad Raees; Ahmad Sufian, Ahmad Syakir; Hassim, Hairul Mubarak (Multidisciplinary Applied Research and Innovation, 2025)
Bird feces significantly impact urban environments, contributing nutrients beyond the needs of algal biomass, resulting in high phosphate concentrations. Traditional bird repellent methods, such as chemicals and physical barriers, often prove ineffective and environmentally harmful. This project addresses the increasing challenge of bird-related disturbances in urban areas, exacerbated by a projected 200% rise in urbanization by 2030. A non-lethal, affordable Mechanical Bird Repellent that employs sound and light to deter birds, aiming to reduce avian waste on vehicles and outdoor surfaces by 50% is produced. Utilizing a 3D-printed body made from ABS and PLA for strength and environmental friendliness, the device integrates a PIR sensor, buzzers, and LED lights. These components activated upon detecting bird movement, creating a sensory overload to the birds that safely repel the birds. Field installation in Pagoh, Johor demonstrated the device's effectiveness, with reductions of more than 50% of bird droppings over two days duration. This innovative solution not only enhances public cleanliness and health by minimizing exposure to harmful bird droppings but also promotes enjoyment of outdoor areas. The project represents a significant advancement in urban wildlife management, providing a practical, efficient, and humane method to maintain cleaner and safer environments.